The viscosity and thrombocytic-aggregation disorders in patients, suffering myocardial infarction with the ST segment elevation - D. Yu. Uzun; V. V. Lazoryshynets; K. S. Uzun (Клінічна хірургія, 2021)
Objective. Analysis of changes in viscosity and disorders of the thrombocytes-aggregation process under impact of various tactical, diagnostic and intervention approaches in patients, suffering myocardial infarction with persistent elevation of ST segment in presence of multivascular affection of coronary arteries.